ANTIMICROBIAL ACTIVITY OF AQUEOUS, ETHANOLIC AND METHANOLIC LEAF EXTRACTS FROM ACACIA SPP. AND Eucalyptus nicholii - Silva, Ermelinda; Fernandes, Sara; Bacelar, Eunice; Sampaio, Ana (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: In Europe, Acacia and Eucalyptus, originate large amounts of biomass, due to their need by industries and otherbiological control, that can be used to extract antimicrobial substances.Materials and Methods: Foliar aqueous, ethanolic and methanolic extracts of Acacia baileyana (Cootamundra wattle), Acaciadealbata (silver wattle), Acacia melanoxylon (black wattle) and Eucalyptus nicholii (narrow-leaved black peppermint) were assessedfor antimicrobial activity against Escherichia coli, Bacillus cereus, Candida albicans and Candida parapsilosis, using the discdiffusion method.Results: Ethanolic extracts from A. baileyana and A. dealbata showed significant (P< 0.05) antimicrobial activity. Concerning themicrobial species tested, differences were found in A. baileyana (P< 0.01) and E. nicholii (P< 0.0001) extracts. These two extractswere effective mostly against B. cereus, followed by C. parapsilosis. According to the antimicrobial activity classification, eucalyptand Cootamundra and silver wattles extracts (both water and ethanol) presented good efficacy against B. cereus, a food poisoningagent, and moderate efficacy against the remaining microorganisms. E. coli, a Gram negative, exhibited low sensibility to all foliarextracts.Conclusion: A. baileyana, E. nicholii and A. dealbata foliar biomass could be used to develop alternative substances in microbialcontrol.